Online Ordering System for Wicked Cinnamon Rolls Home Bakery (e-Bakery) - Wan Afindi, Wan Alyaa Maisarah; Bin Sahid, Dr Mohd Zanes (Applied Information Technology And Computer Science, 2025)
Wicked Cinnamon Rolls are a home bakery which is located in Kota Bharu, Kelantan. This home bakery started their business in early 2021 when the COVID-19 pandemic broke out. Wicked Cinnamon Rolls Home Bakery is still using manual based system to take orders and manage their orders. This has caused them several problems which are lack of an online presence and e-commerce skills, human error and may reduce the effectiveness of the ordering process. The purpose of this project is to create an online ordering system for the home bakery in order to improve customer satisfaction, speed up the process ordering, and expand market reach. The system's design prioritizes offering a comfortable and user-friendly interface for customers to place orders and for the bakery owner to easily manage the process. The methodology used to develop this project is prototyping model. Before developing the final product, a rough version or prototype of the product is created to gather input from the user, test functionality, and refine requirements. Prototyping, assessment, and refining are iterated until the prototype achieves the required objectives and requirements. The system is a web-based system that consists of 9 modules which are register, login, profile user, menu, order, discount, invoice, sales report, and feedback. The proposed system can be used by two types of users which is administrator and customer. With this system, the process of ordering will be ease by both users.